A new basal sauropodiform from South Africa and the phylogenetic relationships of basal sauropodomorphs. (23rd June 2015) - Otero, Alejandro; Krupandan, Emil; Pol, Diego; Chinsamy, Anusuya; Choiniere, Jonah
<x xml:space="preserve">Abstract</x> We present a new medium‐sized basal sauropodomorph, Sefapanosaurus zastronensis gen. et sp. nov., from the Upper Triassic−Lower Jurassic Elliot Formation of South Africa. It is represented by parts of the postcranial skeleton of at least four individuals, including: cervical, dorsal, sacral and caudal vertebrae, most of the forelimb, and part of the hindlimb. Sefapanosaurus bears several autapomorphies of the astragalus, and referred material also shows autapomorphic features. The inclusion of Sefapanosaurus in a phylogenetic analysis places it within the group of sauropodomorphs more closely related to sauropods than to Massospondylus (i.e. Sauropodiformes), increasing the currently known diversity of the so‐called 'transitional forms' leading to Sauropoda. Character optimization revealed the presence of several features that are common for taxa placed within the transitional branches basal to Sauropoda. Sefapanosaurus, together with other transitional sauropodomorphs reported during the last decade, highlights the importance of Gondwanan taxa for understanding the palaeobiodiversity, global distribution, and macroevolutionary changes in the group related to the rise of sauropods. © 2015 The Linnean Society of London